A Highly Sensitive Two‐Photon Ratiometric Probe for Rapid Detection of the hNQO1 Enzyme in Colon Cancer Tissue. Issue 9 (8th February 2019) - Cho, Myoung Ki; Juvekar, Vinayak; Lim, Chang Su; Noh, Choong‐Kyun; Shin, Sung Jae; Kim, Hwan Myung
Abstract: hNQO1 is an intracellular flavoenzyme that protects cells from oxidative stress, redox cycling, and neoplastic lesions that convert endogenous and exogenous quinones to hydroquinone. Since hNQO1 is overexpressed in several human tumor cells, we carried out sensitive and rapid quantitative analyses of hNQO1 in live cells and human colon tissue in detail by utilizing an hNQO1 enzyme selective two‐photon fluorescent probe (SHC‐E ). The probe consists of trimethyl‐locked quinone linked to 6‐(benzo[d]thiazol‐20‐yl)‐2‐(N, N‐dimethylamino)naphthalene (BTDAN) via a para ‐hydroxybenzyl alcohol spacer, which focuses on the trigger group for its easy lactonization after hNQO1‐catalyzed NADH reduction. By changing the N ‐methyl amide group on the self‐cleavable linker to an ester, we achieved high sensitivity and fast response of the probe toward hNQO1. Furthermore, live‐cell imaging withSHC‐E enabled its use in hNQO1 activity studies in HT‐29 cells and hNQO1‐negative cell lines (MDA‐MB‐231 and CCD18Co), whereas deep‐tissue two‐photon imaging of hNQO1 eliminated the need for tissue homogenization. The results show that theSHC‐E ratiometric fluorescence‐based two‐photon sensor is capable of utilizing near‐infrared light as the excitation source for selective detection of the cancer biomarker hNQO1 in vivo, and that it could become a tool for early colon cancer diagnosis where a notable increase in hNQO1 activity is found. Abstract : Double the ratio : A two‐photon excitable and emission‐ratiometric probe (SHC‐E) for detecting the hNQO1 enzyme was developed. This probe exhibited fast and selective response to hNQO1 in situ and can precisely detect the different levels of hNQO1 activity in normal and colon cancer tissues.